2013
DOI: 10.2337/dc12-1577
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Glucose Level and the Risk of Incident Atherosclerotic Cardiovascular Diseases

Abstract: OBJECTIVEAlthough diabetes increases the risk of cardiovascular disease (CVD) and mortality, the dose-response relationship between fasting glucose levels below those diagnostic of diabetes with cardiovascular events has not been well characterized.RESEARCH DESIGN AND METHODSA prospective cohort study of more than one million Koreans was conducted with a mean follow-up of 16 years. A total of 1,197,384 Korean adults with no specific medical conditions diagnosed were classified by baseline fasting serum glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
112
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(126 citation statements)
references
References 36 publications
11
112
0
3
Order By: Relevance
“…On the other hand, hypoglycemia or rapid changes in plasma glucose may lead to elevations of counterregulatory hormones, such as epinephrine and norepinephrine, and these increases induce vasoconstriction and platelet aggregation 3, 15. Furthermore, there is evidence that rapidly increasing glucose concentrations, rather than gradual increases, occur late in diabetes mellitus,16, 17 and individuals with stable FPG concentrations are less likely to develop diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, hypoglycemia or rapid changes in plasma glucose may lead to elevations of counterregulatory hormones, such as epinephrine and norepinephrine, and these increases induce vasoconstriction and platelet aggregation 3, 15. Furthermore, there is evidence that rapidly increasing glucose concentrations, rather than gradual increases, occur late in diabetes mellitus,16, 17 and individuals with stable FPG concentrations are less likely to develop diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the association between FPG and CHD had been extensively studied. Park et al3 reported a J‐shaped association between fasting glucose levels and cardiovascular disease risk across the full range of FPG values. It had also been demonstrated that the angiographic CHD prevalence increases with increasing FPG levels 4.…”
mentioning
confidence: 99%
“…Although diabetes increases the risk of CVD and mortality, the dose-response relationship between a fasting glucose level below that diagnostic for diabetes with cardiovascular events has not been well characterized (12). Impaired fasting glucose should be considered a predictor of the risk of CAD (12) and Shaye et al (13) found that an elevated CVD risk is strongly and independently associated with a glucose level within the normoglycemic range.…”
Section: Discussionmentioning
confidence: 99%
“…Increased fasting glucose levels are related to insulin resistance and thus to the metabolic syndrome with a cascade of cardiovascular risk factors (CRF) [1][2][3][4]. The impact of abnormal glucose metabolism, hypertension and dyslipidemia on cardiovascular morbidity and mortality was demonstrated by numerous epidemiological and clinical studies [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%